Earthquake Dynamic Failure Mechanism of Dangerous Rock Based on Dynamics and PFC3D - Tian, Yun; Wu, Yong; Li, Hongtao; Ren, Bangzheng; Wang, Hao (Frontiers in Earth Science, 2021)
The dynamic failure mechanism of horizontally layered dangerous rock during earthquakes is complex and only few studies have addressed the combination of particle flow code (PFC) meso-level failure mechanism and mechanical analysis. Based on fracture mechanics and material mechanics we establish a calculation method for the interlayer load and stability coefficient of horizontal layered dangerous rock during strong earthquakes. The method was applied for calculating the stability of a horizontally layered dangerous slope along a highway in the Sichuan Province (China) during earthquakes as a case study. Using a 3D particle flow simulation technology, we have constrained a PFC3D model of the horizontally layered dangerous rock. Its dynamic stability, failure mode and Hilbert-Huang 3D time-frequency characteristics are analyzed, and the results of the simulation are largely consistent with the time of the dangerous rock failure as estimated by our new method for calculating the stability of dangerous rocks. Our study documents that as the seismic acceleration gradually increases, the stability coefficient of the rock block fluctuates more violently and the stability coefficient gradually decreases. The stability coefficient of the rock block decreases fastest between 5 and 6s and the reduction in the stability coefficient is between 0.12 and 0.25. Before the seismic acceleration reaches the maximum, the dangerous rock blocks on the two main controlling structures collapse and get destroyed. 25 seconds after the earthquake, the failure mode of the dangerous rock is collapse-slip-rotation. Hilbert–Huang transformation (HHT) analysis documents that earthquakes with frequencies of 0-10Hz and 250Hz have the strongest destructive effect on the stability of horizontally layered dangerous rocks.